Pola Gradual Dalam Al-Qur’an - Muhamad Aroka Fadli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
The Qur'an revealed gradually and have a lot of wisdom, one of the wisdom is humans can adapting whith the positive habits from the negative habits. The Qur’an can change the Sahabah from jahiliyah to golden era and be a chosen people who are blessed by Allah. Way of life the sahabah to be a great man with the Qur’an can duplicated. The gradual model of Qur’an that the aouthor research have three types. The frist, without gradual is all about belief in god. The second, short gradual to change negative habits with education and prohibition. The third, long gradual is all about habits dan culture in community that hard to change and potentially to ruin the community. The procedures of gradual is from allowed to prohibited and from prohibited to allowed.